2020
DOI: 10.1159/000504388
|View full text |Cite
|
Sign up to set email alerts
|

Biological Sex and IgE Sensitization Influence Severity of Depression and Cortisol Levels in Atopic Dermatitis

Abstract: Background: Depression is a common comorbid condition with atopic dermatitis (AD), particularly during the active disease cycle. Controversial results regarding the contribution of biological sex, immunoglobulin E (IgE) sensitization, and cortisol on AD severity and comorbid depression justify further investigation. Objective and Methods: To explore the influence of sex and IgE sensitization on biochemical and psychological parameters, and severity of AD, a case-control study of 105 volunteers (56 AD, 49 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Moreover, dysfunction of the neuroendocrine-immune system was observed in the presence of skin diseases as previously described. Studies have shown that some changes in the metabolism and balance of glucocorticoids and sex hormones may be susceptible factors of immune-mediated diseases ( Kasperska-Zajac et al, 2007 ; Vinnik et al, 2020 ). It has been shown that glucocorticoids, such as cortisol and cortisone, and sex steroids, such as DHEA and testosterone, have multiple immunomodulatory effects ( Bereshchenko et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dysfunction of the neuroendocrine-immune system was observed in the presence of skin diseases as previously described. Studies have shown that some changes in the metabolism and balance of glucocorticoids and sex hormones may be susceptible factors of immune-mediated diseases ( Kasperska-Zajac et al, 2007 ; Vinnik et al, 2020 ). It has been shown that glucocorticoids, such as cortisol and cortisone, and sex steroids, such as DHEA and testosterone, have multiple immunomodulatory effects ( Bereshchenko et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors reported that in AD patients with depressive symptoms and state anxiety, natural killer (NK) activity was reduced along with plasma IL-4 levels. Vinnik et al [ 56 ], on the other hand, identified the increased plasma levels of IgE and cortisol as common pathogenetic mechanisms. The overall risk of bias for this study was high, due to a high score on confounding and information bias.…”
Section: Resultsmentioning
confidence: 99%
“…However, to what extent such mechanisms contribute clarifying the comorbidity presence remains unclear [ 55 ]. Vinnik et al [ 56 ], in addition, indicated the increased plasma levels of IgE and cortisol. Interestingly, the authors hypothesized that particularly in AD male patients, the major active neurosteroid DHEA appeared significant as a regulator of IgE synthesis and eosinophil proliferation, besides the increased cortisol levels and the activated HPA axis response caused by the IgE-mediated degranulation of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activity of hormones in atopic dermatitis (AD) has been demonstrated [ 52 ], with a different dermatological manifestation based on IgE sensitization only in male patients [ 53 ].…”
Section: Sex Differences In Autoimmune Diseases Inflammatory Disorder...mentioning
confidence: 99%